Pemberdayaan Masyarakat Kota Dibidang Budaya Melalui Festival Anak Nagari (FAN) Di Pantai Purus, Padang - Andriani, Desi; Putri, Lili Dasa (Universitas Nusa Cendana, 2022)
Abstract Community empowerment is a very important service activity and must be carried out in an effort to free the community from various adversities, backwardness and backwardness. One of the cities deemed necessary to implement community empowerment activities is Purus Beach, West Padang City. As for the community empowerment activities, the Nagari Children Festival event was held. This nagari children festival event is intended to explore, promote, and preserve cultural arts around the city of Padang through the nagari children's games, which are organized by the Association of Indonesian Tourism Ambassadors (ADWINDO) of Padang City and under the auspices of the Padang City Tourism Office on March 6, 2022. owned by a nagari child who was buried by the time At Purus Beach, West Padang City, this event is a big step in promoting, and preserving the culture of, tourism development. The effectiveness of this FAN activity at Purus Beach, Padang City on March 6, 2022 as a solution to cultural and environmental problems around Purus Beach is very effective because this activity's main goal is to revive children's and youth's interest in playing local games which as we can see at this time, most children and teenagers rarely play local games such as cakbur, cocky, galah and others.